A comparison of two different software packages for the analysis of body composition using computed tomography images - Rollins, Katie E.; Awwad, Amir; MacDonald, Ian A.; Lobo, Dileep N. (Elsevier, 2018)
Objectives: Body composition analysis from computed tomography (CT) imaging has become widespread. However, the methodology used is far from established. Two main software packages are in common usage for body composition analysis, with results used interchangeably. However, the equivalence of these has not been well established. The aim of this study was to compare the results of body composition analysis performed using the two software packages to assess their equivalence.